Inductive constructivism and national identities: letting the data speak. Issue 4 (9th May 2017) - Alemán, José; Woods, Dwayne
Abstract: The literature on nationalism has provided conceptual definitions of national identity that supposedly delineate its underlying empirical manifestations. A binary conceptualization (civic versus ethnic) is widely used by scholars. There are confusion and ambiguity in the definition, however, as well as sense that the prevailing schema does not adequately capture the fluidity and complexity of the phenomenon. We posit that abstract conceptual definitions do not validly capture the way individuals actually experience identification with their nations. Using a methodology that models the distribution of responses to survey questionnaires – latent class analysis – we demonstrate that individuals cluster in two different groups in the way they identify with their nations: nationalists are strongly attached to the nation and more exacting in their criteria for membership, while cosmopolitans display lower identification with the nation and are more inclusive in their desired criteria of membership. These classes are to some degree fluid across indicators and nations. Broadly speaking, however, the configurations are comparable cross‐nationally.